AGAMA DAN FEMINISME: ANTARA DOKTRIN TEKS DAN REALITAS SOSIAL (Studi Aplikatif ayat “Al-Rijaalu Qawwaamuuna ‘Ala Al-Nisaa’” terhadap Model Pembagian Kerja Suami - Istri Di Kalangan Elite Agama Di Kepanjen Jombang) - Mochammad Agus Rachmatulloh (lp2m-uin malang, 2008)
Circle of elite religion in Kepanjen ossume leadership in absolute family to men with interest emphasize at condition and situation, hemce the leadership remain to be holded by husband with various rule, not because of various reason so that used by interpretation is paradigm of patriarkhi-sentris moderating. Relation that happened betwen other member and husband-wife is equiping each other one anather with center couduct remain to husband on condition that can execute duty and his obligation. Application is design divisoon of labor of husband-wife as according to perpective of gender, domiciling husband remain to as wife and leader as adjancented and olso in public region and house wifeny, husband and wife to domicili well balanced with position as parallel partner, in duty obligation of husband and wife, all absolute nothing that, but can be done together with move is emplosizing of flexibility and counditional, and also the existence of feeling volunter and ridhoeach other.Keywords: interpretation and application.